2017
DOI: 10.1111/hiv.12488
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome 2B6 polymorphism and efavirenz‐induced central nervous system symptoms : a substudy of the ANRS ALIZE trial

Abstract: The deficient CYP2B6 516 T allele is associated with higher efavirenz plasma drug levels and more frequent CNS-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
0
21
1
Order By: Relevance
“…This could be due to the fact that slow metabolizers eliminate drugs from the system slowly, thus leading to drug persistence resulting in toxicity. Our results can be compared to other studies that reported an association between the presence of 516G>T or 983T>C, high plasma NVP or EFV concentrations and the susceptibility to related ADRs 16,2931,33,44. The lack of a significant difference between the presence of the adverse events and the genotypes might have been due to the small sample size, particularly the number of cases, which is one of the limitations of this study.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…This could be due to the fact that slow metabolizers eliminate drugs from the system slowly, thus leading to drug persistence resulting in toxicity. Our results can be compared to other studies that reported an association between the presence of 516G>T or 983T>C, high plasma NVP or EFV concentrations and the susceptibility to related ADRs 16,2931,33,44. The lack of a significant difference between the presence of the adverse events and the genotypes might have been due to the small sample size, particularly the number of cases, which is one of the limitations of this study.…”
Section: Discussioncontrasting
confidence: 39%
“…These two polymorphisms have been associated with increased EFV and NVP plasma levels in several studies 2028. A number of associations between these human genetic variants, high drug level and predisposition to ARV drug toxicity have been described in recent years 2933. ADRs associated with NVP are cutaneous or dermatological events (toxidermia/hypersensitivity, skin rash, and pruritus).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, 516G>T plays a significant role in EFV concentrations, especially in children older than 10 years [74]. Moreover, higher EFV plasma levels and CNS-related complications are observed in patients deficient in CYP2B6 516T allele [75]. 516G>T variant is most common in the South Asian population, while least frequently observed in East Asians [69].…”
Section: Polymorphism Of Cyp Enzymes Affecting Pharmacodynamics Of Cymentioning
confidence: 99%
“…Efavirenz is oxidized mainly by hepatic cytochrome P450, family 2, sub-family B, polypeptide 6 (CYP2B6) isozyme. The CYP2B6 gene is highly polymorphic [ 215 ] and the CYP2B6 c.516 G>T variant appears to strongly predict the pharmacokinetics of Efavirenz [ 216 ]. That is, this 516G>T change, specifically in HIV-infected individuals of African-ethnicity, genetically predisposes these patients (“slow Efavirenz metabolizers”) to develop adverse CNS reactions with a frequency of 34–50% [ 215 , 217 ].…”
Section: Drug Metabolism/transporter Genesmentioning
confidence: 99%